2013
DOI: 10.1080/19371918.2013.774811
|View full text |Cite
|
Sign up to set email alerts
|

Does Cultural Adaptation Have a Role in Substance Abuse Treatment?

Abstract: The changing ethnic composition of the nation and increasing requirements to use evidence-based treatments (EBTs) challenge mental health professionals to adapt treatments and interventions to be appropriate for their clients. This article applies the available information on cultural adaptation to substance abuse. The authors’ review suggests that the most common approaches for adapting substance use interventions include some combination of either community involvement in the adaptation, existing research an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 72 publications
2
31
0
Order By: Relevance
“…Similarly to other studies (e.g., Acevedo et al, 2012; Montgomery, Burlew, Kosinski, & Forcehimes, 2011), the current study suggests that African American and White substance users may have different treatment needs that may call for culturally-tailored interventions (Burlew, Copeland, Ahuama-Jonas, & Calsyn, 2013). For example, Brown, Hill and Giroux (2004) conducted a focus group with rural African American cocaine users who suggested that interventions should involve friends and family and provide direct resources (job, car, housing) or assistance in receiving these resources in treatment.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly to other studies (e.g., Acevedo et al, 2012; Montgomery, Burlew, Kosinski, & Forcehimes, 2011), the current study suggests that African American and White substance users may have different treatment needs that may call for culturally-tailored interventions (Burlew, Copeland, Ahuama-Jonas, & Calsyn, 2013). For example, Brown, Hill and Giroux (2004) conducted a focus group with rural African American cocaine users who suggested that interventions should involve friends and family and provide direct resources (job, car, housing) or assistance in receiving these resources in treatment.…”
Section: Discussionsupporting
confidence: 79%
“…By definition, an EBI’s effectiveness is determined by its capacity for, “producing Y outcomes for X population at time T, [and] in setting S.” (Gottfredson, Cook, Gardner, et al, 2015, p. 286). However, when an EBI exhibits a lower effectiveness across one or more of these factors, this would indicate an erosion in the EBI’s social validity as implemented within a new population (Burlew et al, 2013; Lau 2006). As a remedy, strategic modifications would be indicated to improve the original EBI’s performance because it: (a) exhibits lowered effectiveness in changing targeted outcomes for a subcultural group, or (b) the new subcultural group exhibits unique social or clinical problems that are not addressed by the original EBI (Barrera & Castro, 2006; Lau, 2006).…”
Section: Linking Ebis To the Elimination Of Health Disparities And Inmentioning
confidence: 99%
“…The adaptations of the deep structural dimension contemplate the cultural, social, historical, environmental and psychological factors that influence the behaviors of the population in focus. It refers to the values or meanings, leading to the revision or modification of the central components of the intervention 27 . The modification of these should be guided by the inclusion of specific risk and protective factors of the population 21 .…”
Section: The Adoption / Preparationmentioning
confidence: 99%
“…The initial results indicate that adaptation to the context, denominated cultural adaptation according to authors, should be explored as a process and not as a punctual stage as presented in the literature 4,9,11,19,[25][26][27] . The experiences of the implantation of practices based on evidence in new contexts highlight the need of adaptation in order to increase the cultural relevance of the intervention as well as to make the program compatible with the language, dialect, values and cultural meanings of the new audience [28][29][30] .…”
mentioning
confidence: 99%
See 1 more Smart Citation